Ketika Apologetika Berujung Pidana - Julitinus Harefa; Harman Ziduhu Laia; Elisua Hulu (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
This writing employs a qualitative approach to the method of literature research. In their apologetic activities, several Indonesian Christian apologists ended up in court because they were caught in blasphemy laws. The reason is that Christian apologists often consider acts of offense (attacking) other religious beliefs to be included in the scope of Christian apologetics. The Bible does not justify acts of apologetics to insult and demean other religious beliefs but to correct existing misunderstandings. An arrogant attitude in apologetics will cause new problems for apologists by trying to build a wall of enmity (separator) between opponents and the gospel that is conveyed so that it opens opportunities for the gospel to be reviled and rejected, as well as building a bad mindset about the gospel because Christian apologetics is not to win an argument but to pave the way for preaching the Gospel of Christ. Because the success of an apologist lies in a respectful and gentle attitude and behavior accompanied by a pure heart. So the research objective of this scientific paper is to expose the attitude that Indonesian apologists should have and to open the curtain on understanding misunderstandings in understanding offense perspective apologetics.